1985
DOI: 10.1093/ajcn/42.3.495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increased amounts of pectin on a solid-liquid meal digestion in healthy man

Abstract: The effect of three concentrations of high-methoxy apple pectin (5, 10, and 15 g), on solid-liquid meal digestion was studied in 12 healthy men by the gastrointestinal intubation technique. The gastric emptying of water and carbohydrates is significantly reduced only after 10 and 15 g pectin. The changes in gastric pH are similar for pectin-free and pectin-containing meals. Cumulative lipase and trypsin outputs are not significantly different with and without pectin. When gastric uronic acid concentration is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 17 publications
0
12
2
Order By: Relevance
“…Viscous soluble fibers such as pectin have negligible effects on the secretion of CCK [16]. Juvonen et al [34] demonstrated that high viscosity has no effect on the production of gut hormones.…”
Section: Induction Of Satiety Hormonesmentioning
confidence: 99%
“…Viscous soluble fibers such as pectin have negligible effects on the secretion of CCK [16]. Juvonen et al [34] demonstrated that high viscosity has no effect on the production of gut hormones.…”
Section: Induction Of Satiety Hormonesmentioning
confidence: 99%
“…Therefore, the impact of its consumption on the host microbiota is of particular interest. iii) Dietary fibers like pectins are important for nutritional companies because of their cheap production and their beneficial effects on reducing glucose absorption, hypocholesterolemic effects and delayed gastric emptying [31], [32]. Moreover, pectins may reduce the generation of ammonia [33] and the adhesion of pathogens to intestinal epithelial cells [34] in addition to their contribution in maintaining intestinal integrity [35].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of soluble dietary fibres into liquid meals enhances meal viscosity and results in the formation of a gel. Viscous gel‐forming fibres, such as pectin and guar, delay GE and nutrient absorption 6–9 . In practice, fibre supplementation is indicated for the control of post‐prandial hyperglycaemia in diabetes and in order to slow the absorption of nutrients in dumping syndrome 10 .…”
Section: Introductionmentioning
confidence: 99%